Complications of Trauma Patients Admitted to the ICU in Level I Academic Trauma Centers in the United States. (2nd June 2014) - Mondello, Stefania; Cantrell, Amy; Italiano, Domenico; Fodale, Vincenzo; Mondello, Patrizia; Ang, Darwin
Abstract : Background . The aims of this study were to evaluate the complications that occur after trauma and the characteristics of individuals who develop complications, to identify potential risk factors that increase their incidence, and finally to investigate the relationship between complications and mortality. Methods . We did a population-based retrospective study of trauma patients admitted to ICUs of a level I trauma center. Logistic regression analyses were performed to determine independent predictors for complications. Results . Of the 11, 064 patients studied, 3, 451 trauma patients developed complications (31.2%). Complications occurred significantly more in younger male patients. Length of stay was correlated with the number of complications ( R = 0.435, P < 0.0001 ) . The overall death rate did not differ between patients with or without complications. The adjusted odds ratio (OR) of developing complication for patients over age 75 versus young adults was 0.7 ( P < 0.0001 ) . Among males, traumatic central nervous system (CNS) injury was an important predictor for complications (adjusted OR 1.24). Conclusions . Complications after trauma were found to be associated with age, gender, and traumatic CNS injury. Although these are not modifiable factors, they may identify subjects at high risk for the development of complications, allowing for preemptive strategies for prevention.